Reactive Noble-Gas Compounds Explored by 3D Electron Diffraction: XeF2-MnF4 Adducts and a Facile Sample Handling Procedure - Motaln, Klemen; Gurung, Kshitij; Brázda, Petr; Kokalj, Anton; Radan, Kristian; Dragomir, Mirela; Žemva, Boris; Palatinus, Lukáš; Lozinšek, Matic (ACS central science, 2024)
Recent advances in 3D electron diffraction (3D ED) have succeeded in matching the capabilities of single-crystal X-ray diffraction (SCXRD), while requiring only submicron crystals for successful structural investigations. One of the many diverse areas to benefit from the 3D ED structural analysis is main-group chemistry, where compounds are often poorly crystalline or single-crystal growth is challenging. A facile method for loading and transferring highly air-sensitive and strongly oxidizing samples at low temperatures to a transmission electron microscope (TEM) for 3D ED analysis was successfully developed and tested on xenon(II) compounds from the XeF2-MnF4 system. The crystal structures determined on nanometer-sized crystallites by dynamical refinement of the 3D ED data are in complete agreement with the results obtained by SCXRD on micrometer-sized crystals and by periodic density-functional theory (DFT) calculations, demonstrating the applicability of this approach for structural studies of noble-gas compounds and highly reactive species in general. The compounds 3XeF2·2MnF4, XeF2·MnF4, and XeF2·2MnF4 are rare examples of structurally fully characterized xenon difluoride-metal tetrafluoride adducts and thus advance our knowledge of the diverse structural chemistry of these systems, which also includes the hitherto poorly characterized first noble-gas compound, "XePtF6".